Permacrises and Polycrises: Outlining the Contemporary Security Environment through References to Strategic Documents of Regional and International Actors - Koukakis, Georgios (HAPSc Policy Briefs Series, 2023)
The contemporary security environment has been characterised as an environment of permacrises and polycrises, indicating the simultaneous occurrence of crises in different fields, which is evident in a plethora of strategic documents containing relevant references that indicate the existence or emergence of a variety of threats and risks. The purpose of this analysis is to highlight the main threats and risks of the contemporary security environment through a comparative analysis of several strategic documents of international and regional actors.